Genetic Analysis of the LOXHD1 Gene in Chinese Patients With Non-Syndromic Hearing Loss - Wang, Wei-Qian; Gao, Xue; Huang, Sha-Sha; Kang, Dong-Yang; Xu, Jin-Cao; Yang, Kun; Han, Ming-Yu; Zhang, Xin; Yang, Su-Yan; Yuan, Yong-Yi; Dai, Pu (Frontiers in Genetics, 2022)
Non-syndromic hearing loss (NSHL) is a common neurosensory disease with an extreme genetic heterogeneity which has been linked to variants in over 120 genes. The LOXHD1 gene (DFNB77), encoding lipoxygenase homology domain 1, is a rare hearing loss gene found in several populations. To evaluate the importance of LOXHD1 variants in Chinese patients with NSHL, we performed genetic analysis on LOXHD1 in 2,901 sporadic Chinese patients to identify the aspect and frequency of LOXHD1 causative variants. Next-generation sequencing using a custom gene panel of HL was conducted on 2,641 unrelated patients and whole-exome sequencing on the remaining 260 patients. A total of 33 likely causative variants were identified in 21 patients, including 20 novel variants and 13 previously reported pathogenic variants. Each of the 20 novel variants was evaluated according to ACMG criteria. These findings showed that causative variants in LOXHD1 were found in about 0.72% (21/2,901) of Chinese NSHL patients. This study is by far the largest number of novel variants identified in this gene expanding the range of pathogenic variants in LOXHD1, and suggests that variants in this gene occur relatively commonly in Chinese NSHL patients. This extensive investigation of LOXHD1 in Chinese NSHL patients proposed six recurrent LOXHD1 variants. These findings may assist in both molecular diagnosis and genetic counseling.